OA02.13. Effects of drakshavaleha in developing mice embryo - Kumar, Sunil (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: Due to antianemic properties and nutritional values, Drakshavaleha has been used as a Naimittika Rasayana (promoter of specific vitality in specific disease) to a woman during her pregnancy expecting a good health of both mother and her offspring. The objective of the study was to investigate a protective effect of Drakshavaleha against Cyclophosphamide (CP) induced growth retardation in mice pups in the terms of body weight and CRL (crownrump length). METHOD: Group I (Control): Pregnant mice (n=10) received 0.2 ml of distilled water intraperitoneal on day 11 of pregnancy as vehicle. Group II (Drakshavaleha): Pregnant mice (n=10) received Drakshavaleha (16g/ kg) orally from day ‘0’ to day ‘18’ of pregnancy. Group III (CP): Pregnant mice (n=10) received CP (10mg/kg) intraperitoneal on day 11 of pregnancy. Group IV (CP + Drakshavaleha): Pregnant mice (n=10) received CP (10mg/kg) intraperitoneal on day 11 under cover of Drakshavaleha (16 g/kg) orally from day ‘0 to day 18’ of pregnancy. RESULT: In Group III, growth retardation and decreased fetal weight were seen when CP was injected on 11th day of gestation. Amongst litters whose mothers received the drug (CP) on same day in same dose under Drakshavaleha cover the pups were seen with significant weight gain which however was lower as compared to the pups born to mothers with administration of Drakshavaleha alone (Group II). CR length was also of same conclusion in group II and group I respectively. CONCLUSION: The above observations suggest that Drakshavaleha increases the size and weight of pups when it given to the mother mice during their gestation period.